Hydrodynamic Performance of High-Speed Craft: A CFD Study on Spray Rails - Muhammad Sulman; Simone Mancini; Rasul Niazmand Bilandi; Luigi Vitiello (Journal of Marine Science and Engineering, 2025)
In high-speed crafts, whisker spray increases viscous resistance by enlarging the wetted surface near the stagnation line. Spray rails (SRs) mitigate this issue by redirecting water flow, reducing the wetted surface, and lowering overall resistance. This study investigates the effect of SRs on the hydrodynamic performance of the C1 hull of Naples Systematic Series (NSS), focusing on the systematic variations in size, number, and placement. Numerical simulations, validated with towing tank results, were conducted using STAR CCM+ 2306. Mesh independence analysis was also performed to optimize computational efficiency. Key findings highlight the critical role of SR design in performance optimization. Wider SRs (e.g., three per side, 0.96% LWL) reduced resistance by up to 8.5% at high speeds (Fr∇= 3.26), but slightly increased the resistance at lower speeds (~2%) due to a larger wetted surface. Narrower SRs (e.g., three per side, 0.48% LWL) achieved resistance reductions of up to 4.6%, while configurations with multiple SRs (e.g., three per side, 0.72% LWL) outperformed single-rail designs by reducing resistance up to 4%. Placement near the chine proved more effective than near the keel, offering a 4% additional reduction in resistance. Additionally, SRs generated lift, raising the hull, and reducing immersion. The study underscores the importance of optimizing SR size, number, and placement to enhance hydrodynamic efficiency, particularly for high-speed operations.

Numerical Investigation of Single and Double Steps in Planing Hulls - Muhammad Sulman; Simone Mancini; Rasul Niazmand Bilandi (Journal of Marine Science and Engineering, 2024)
Incorporating steps into a hull reduces the wetted surface, promoting improved hydrodynamic lift and reduced resistance at high speeds, provided that the step is designed appropriately. Traditional hydrodynamics studies rely on scaled model testing in towing tanks, but numerical tools offer a more efficient alternative. This study focused on investigating the hydrodynamic performance of stepped hulls by modifying the parent hull of the Naples Systematic Series (C1). The Computational Fluid Dynamics (CFD) code SIEMENS PLM STAR CCM+ version 2302 was used for simulations, including four different beam Froude numbers (FrB = 1.13, 2.22, 2.56, and 2.96) and a total of 15 hull configurations with single and double steps. By employing a three-dimensional computational analysis of multiphase flow using Dynamic Fluid–Body Interaction (DFBI) and overset mesh, various performance parameters such as resistance coefficient, dimensionless wetted surface, sinkage, and dynamic trim were analyzed. The accuracy of the CFD results was confirmed through comparison with experimental data and grid uncertainty assessment. The study demonstrated that placing a single step near the transom decreased trim and increased resistance and wetted surface. Conversely, positioning a step in the forward section reduced the trim angle at lower step heights but increased trim at higher step heights in single-stepped hulls. The application of these findings contributes to the design optimization of stepped hulls for enhanced performance in high-speed maritime applications.

A novel WDR62 mutation causes primary microcephaly in a Pakistani family - Mazhar Mustafa Memon; Syed Irfan Raza; Sulman Basit; Rizwana Kousar; Wasim Ahmad; Muhammad Ansar (Molecular Biology Reports, 2013)

Genetic mapping of an autosomal recessive postaxial polydactyly type A to chromosome 13q13.3–q21.2 and screening of the candidate genes - Umm-e-Kalsoom; Sulman Basit; Syed Kamran-ul-Hassan Naqvi; Muhammad Ansar; Wasim Ahmad (Human Genetics, 2012)

Novel mutations in the keratin-74 (KRT74) gene underlie autosomal dominant woolly hair/hypotrichosis in Pakistani families - Naveed Wasif; Syed Kamran ul-Hassan Naqvi; Sulman Basit; Nadir Ali; Muhammad Ansar; Wasim Ahmad (Human Genetics, 2011)

DFNB89, a novel autosomal recessive nonsyndromic hearing impairment locus on chromosome 16q21-q23.2 - Sulman Basit; Kwanghyuk Lee; Rabia Habib; Leon Chen; Umm-e-Kalsoom; Regie Lyn P. Santos-Cortez; Zahid Azeem; Paula Andrade; Muhammad Ansar; Wasim Ahmad; Suzanne M. Leal (Human Genetics, 2011)

Genetic mapping of a novel hypotrichosis locus to chromosome 7p21.3–p22.3 in a Pakistani family and screening of the candidate genes - Sulman Basit; Ghazanfar Ali; Naveed Wasif; Muhammad Ansar; Wasim Ahmad (Human Genetics, 2010)